(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2025)
This study conducts a pragmatic analysis of selected biblical texts, employing speech act theory, implicature, and discourse analysis to elucidate their functional meanings. Structured in IMRAD format, it outlines methods for textual examination, presents results from key examples, discusses implications for biblical interpretation, and concludes with insights into the broader role of pragmatics in religious discourse.